Comparison of ethanologenic potential of Saccharomyces cerevisiae and Metschnikowia cibodasensis employing watermelon pulp hydrolysate (Zoo Botanica, 2025)
The agricultural sector in Pakistan, which is a major contributor to its economy, produces massive biomass waste such as watermelon leftovers. This paper discusses how watermelon pulp can be used as feedstock in bioethanol production and how this is a viable solution to the energy requirements of Pakistan as well as solving the problem of waste management. Fermentable sugars are found in abandoned watermelons, which can be used as a source of bioethanol. In this study, the objective was to hydrolyze the watermelon pulp Bacillus cereus FA3 using optimum conditions and ferment the resulting saccharified monomers into ethanol, utilizing yeasts; Metschnikowia cibodasensis Y34 strain and Saccharomyces cerevisiae K7 strain. To optimize the experimental conditions for hydrolysis and fermentation, Plackett-Burman and central composite designs (CCD) were developed. Under the optimized conditions of the Plackett-Burman model, i.e., 37°C, pH 4, 50:55mL buffer to pulp ratio, 0.63 IU enzyme dosage, 5 days hydrolysis period, maximum reducing sugars of 45.13±0.01 and total sugars of 82.64±0.06 g/L was achieved. Under the optimized conditions viz. 75:25% hydrolysate: synthetic media, 5% (v/v) of yeast inocula, 25 °C, 15 days, the maximum ethanol yield and content with yeast Metschnikowia cibodasensis Y34 strain was recorded as 0.43 ± 0.007g/g and 13.6 ± 0.008g/L whereas Saccharomyces cerevisiae yielded 0.41 ± 0.004g/g and 12.2 ± 0.001g/L ethanol respectively. These outcomes underscore the effectiveness of the optimized fermentation process and the promising potential of watermelon pulp valorization for sustainable ethanol production.
Keywords: Watermelon pulp waste; bioethanol production; agro-waste valorization; enzymatic hydrolysis; sustainable energy